Dampak Reverse Stock Split terhadap Nilai Perusahaan yang Terdaftar di Bursa Efek Indonesia - Budiarti, Evelin; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2019)
Maximizing the firms value is one of the company’s goals in running its business. The value of a company is often affected by the share price. The stock price itself changes because of the demand and supply in the market. In making investment decisions, investors consider several factors, such as information of corporate actions. Reverse stock split is one type of corporate action. The purpose of this study is to obtain empirical evidence regarding differences of firms value before and after reverse stock split. This research was conducted at companies published on the Indonesia Stock Exchange in 2009-2018. Samples were selected using purposive sampling method so as many as 15 companies were obtained. The data analysis technique used in this study was the Wilcoxon test. The results of this study indicate there is no difference of firms value between before and after a reverse stock split. Keywords : Reverse Stock Split; Stock Split Down; Firms Value.